Unraveling the Hidden Diversity of Gut Microbiota: A Genome Sequencing and Comparative Genome Analysis of Novel Bacterial Strains in Human Stool - Malik, Muhammad Imran; Iram, Ayesha; Khan, Abuzar Mehdi; Qasim, Muhammad; Abbas, Waseem; Munir, Maha (Indus Journal of Bioscience Research, 2025)
E. coli strains have been isolated and identified in Pakistan, but detailed genomic data specific to these strains is still lacking. This gap in knowledge prevents a full understanding of E. coli’s genomics in the region. Research indicates that both phagocytic and nonphagocytic mammalian cells can use Shigella, Listeria, Salmonella and invasive E. coli as vectors for gene delivery. This study seeks to investigate the epidemiology and pathogenic features of E. coli in Pakistan. Stool samples were collected from various regions exhibiting severe symptoms and the bacteria were isolated, cultured and analyzed. The process included DNA extraction, 16s PCR analysis and genome sequencing. Key features of the Escherichia coli SWL-1 genome are a GC content of 50.8%, 5020 coding sequences, 61 RNA sequences and 4 contigs. The genome encompasses genes related to cofactors, vitamins, cell walls, capsules, virulence, disease defense, potassium metabolism and carbohydrates, among others. E. coli strains are categorized into six main types: ETEC, EIEC, EPEC, EHEC, EAEC and DAEC, each causing different levels of diarrhea. Urinary tract infections (UTIs) are the most common extraintestinal infections caused by uropathogenicE. coli (UPEC). Additionally, ExPECE. coli features adhesin operons specific to the antigen, including the virulence genes.